Diacylglycerol kinase ζ regulates microbial recognition and host resistance to Toxoplasma gondii - Liu, Cheng-Hu (The Rockefeller University Press, 2007)

(untitled)
Mammalian Toll-like receptors (TLRs) recognize microbial pathogen-associated molecular patterns and are critical for innate immunity against microbial infection. Diacylglycerol (DAG) kinases (DGKs) regulate the intracellular levels of two important second messengers involved in signaling from many surface receptors by converting DAG to phosphatidic acid (PA). We demonstrate that the ζ isoform of the DGK family (DGKζ) is expressed in macrophages (Mφ) and dendritic cells. DGKζ deficiency results in impaired interleukin (IL) 12 and tumor necrosis factor α production following TLR stimulation in vitro and in vivo, increased resistance to endotoxin shock, and enhanced susceptibility to Toxoplasma gondii infection. We further show that DGKζ negatively controls the phosphatidylinositol 3–kinase (PI3K)–Akt pathway and that inhibition of PI3K activity or treatment with PA can restore lipopolysaccharide-induced IL-12 production by DGKζ-deficient Mφ. Collectively, our data provide the first genetic evidence that an enzyme involved in DAG/PA metabolism plays an important role in innate immunity and indicate that DGKζ promotes TLR responses via a pathway involving inhibition of PI3K.